Temperature at the tool-chip interface in cryogenic and dry turning of AISI 4340 using carbide tool - A. Raof, Natasha; A. Ghani, Jaharah; Che Haron, Che Hassan; Syarif, Junaidi; Abdul Hadi, Musfirah (2016)
A localized high temperature area occurring at the tip of the tool during a cutting process can be detrimental and lead to a rapid wear mechanism. This paper presents the effect of a cryogenic application during the machining process on the temperature generated at the tool-chip interface, compared to a dry environment in the turning of the AISI 4340 alloy steel using a coated carbide tool. The cutting temperature was estimated using the Third Wave AdvantEdge software, which then was validated with the turning experiments. A significant reduction of the cutting temperature and the steeper temperature gradients on the cutting edge and the chips were observed in the cryogenic machining, which indicates more effective heat removal from the cutting zone. The sudden cold of -196 °C caused the chips to become hard and brittle, which enhanced the chip breakability during the machining process.